Penerapan Bottom-up Approach sebagai Dasar Pembelajaran Penerjemahan PKM Remaja Masjid Jami Baiturrahman Jakarta Barat - Ayu Bandu Retnomurti; Nurmala Hendrawaty (LPPM UNIVERSITAS ISLAM KADIRI, 2020)
The purpose of this community service is how to implement the bottom-up approach is used as a basis for Indonesian-English or English-Indonesian translation learning for teenagers of Jami Baiturrahman Mosque in West Jakarta Even Semester 2018/2019. It focuses on: (1) translation theory must be mastered by students so that learning objectives are achieved and must be adapted to the cultural context of the source language; (2) various basic translation strategies; (3) translation teaching materials are arranged from an easy level to a difficult level in accordance with the school level; (4) learning material is developed with learning media that can motivate students; (5) community service team and youth work together to create conducive learning situations; (6) the use of infrastructure and learning media is sufficiently adjusted to the place of learning; (7) evaluation of translations is based on the accuracy, fairness, and clarity of the text. Based on the evaluation, there are still some students make repeated translation errors in the use of grammar, interpret idioms and look for the equivalent of the language from the source into the target language.